Application of 2-dimensional video analysis by competitive swimming coaches to monitor fatigue in breaststroke technique during training - Thow, J. L. (University of Edinburgh, 2016)
In swimming, technical performance is a vital indicator of successful performance; however, during phases of high-intensity training, technique can be negatively influenced by fatigue. Advances in video technology have made it possible to increase coaches` capacity to monitor athletes` technical performances during training. Yet research examining the biomechanical responses that occur with fatigue using video methods, which are applicable and relevant to coaches during training, is scarce. The limited research to date that has examined the biomechanical responses that occur with fatigue has been restricted to examining fatigue during race-like situations and have used technology which is not available for use by coaches during training. Whilst this research indicates that changes occur during races, it does not apply to coaches for use during training. As fatigue, and its management, is a vital component of the training process, identifying a method of monitoring fatigue during training, which is applicable to coaches, is essential for athlete development. This research is therefore intended to address this by exploring the implications of 2-dimensional (2-D) video analysis in the management of fatigue, during training, by competitive swimming coaches. To explore this, this thesis comprises of four studies. The aim of the first study was to investigate whether 2-D video analysis methods currently used by coaches can measure data validly and reliably. To achieve this, the accuracy, precision, reliability and validity of thirty-five variables (thirty-four technical measures and swim time) were calculated using Dartfish Pro Suite motion analysis software, version 6.0 (Dartfish Ltd, Fribourg, Switzerland) and compared to the smallest worthwhile change. By calculating and comparing these measures, only those technical variables which can be measured with accuracy and precision could be determined objectively. A series of fifteen variables (fourteen technical measures and swim time) were found to be precise, valid and reliable when measured using Dartfish Pro Suite motion analysis software, version 6.0. Using the previously established technical measures, the aim of the second study was to assess if these measures can determine whether technical changes can occur during a high-intensity training session. To achieve this, a group of seventeen elite breaststroke swimmers completed a standard swim set. This involved repeating maximal effort 100m swims on a limited swim-rest time, designed to induce a fatigued state representative of high-intensity training conditions. To determine whether technical changes as a result of fatigue could be detected, the fourteen kinematic technique variables and swim time (fifteen dependent variables in total) were recorded and analysed using 2-D Dartfish Pro Suite motion analysis software, version 6.0 from video recordings of the first and last 100m swim of each swimmer. In addition, 95% confidence intervals were determined to investigate any commonalities or individual differences among swimmers in changes in technical parameters. It was found that during one high-intensity session, technical changes can occur in a group of elite swimmers. The largest changes were shown in leg glide duration (64.6%), swim time (33.2%), stroke rate (35.3%), stroke length (-29.2%), and average velocity (-10.2%) and were shown to have statistically significant (p < 0.05) differences between the first and last 25m of the swim set. These changes were also shown to be common amongst all swimmers and occurred early in the swim set. To evaluate coaches understanding of fatigue and its management during training, the aim of the third study was to assess coaches` current practices and knowledge regarding fatigue during training. To achieve this, a questionnaire was distributed to over 370 coaches throughout the UK. The questionnaire was separated into multiple sections which assessed: coaches` current understanding of the topic of fatigue; the methods coaches` employ to monitor fatigue during a training session; and the processes used to manage fatigue during the training process. It was found that up to 98% of the coaches consider fatigue, its effect and management important in the development of their swimmers. Despite this, there is a lack of consistency in knowledge and methods used by coaches to monitor this. As a result, coaches are continuing to use traditional methods to monitor their athletes which are quick and reliable, specifically stopwatches (100%) and visual observation (98%). Due to the predominant use of visual observation to monitor fatigue, and the identification of technical changes with fatigue, the aim of the fourth study was to assess whether coaches could visually identify changes in the previously established technical markers and whether this could be improved through education of fatigue and video analysis methods. To achieve this, two groups of ten competitive swimming coaches observed a series of videos of three swimmers taken pre- and post- training, and were asked to identify any technical factors which they perceived to change. One group underwent an intervention using Dartfish Pro Suite motion analysis software, version 6.0 and underwater analysis to assess whether this improved their ability to visually observe fatigue in elite swimmers. The remaining group of coaches acted as a control group and received no feedback. Following the one hour intervention, the coaches` observations slightly improved, however this improvement was not statistically significant (p > 0.05) nor retained after 4 weeks. Although the coaches` perceptions of fatigue during training varied, they did show a keen interest in further training and education on fatigue and 2-D video analysis. The results from this research indicate that 2-D video analysis is an effective and useful tool, which has practical applications: in monitoring fatigue during a training session; guiding training programmes to maximise training potential; and developing coaches` identification and management of fatigue during training through education programmes.